The use of false discourses. A Plato’s justification in Philo of Alexandria (Republic 376-414 and Quod Deus sit inmutabilis 51-69) (Circe de clásicos y modernos, 2018)
This study supports the thesis that Philo of Alexandria would have adopted a Platonic argument related to the positive value of false discourses. Indeed, the Philonic idea that certain narratives can be a “beneficial falsehood” (Deus 64) reissues –as this study tries to show– the famous concept of “noble lie”, coming from Plato (R. 414). Based on the analysis of the pertinent texts, this study concludes that, according to the Alexandrian –like Plato–, some false narratives can play a role, referring to true contents.
Keywords: noble lie; myth; anthropomorphism; interpretation; falsehood